The industrial and Commercial Workers' Union of Africa - Wickins, P L (School of Economics, 2016)
The present study has three aims. Firstly it endeavours to give a detailed, though not exhaustive, history of the I.C.U. in broadly chronological sequence, to show how it was organised and to record what its leaders were doing, saying and thinking at any given time. Quotations are introduced rather freely in the belief that they transmit thoughts and feelings more perfectly and more vividly and often more succinctly than do paraphrases. Some of the detail, which may at first sight seem trivial and otiose, has been included deliberately in an attempt to build up, a pointillist picture that conveys more in its entirety than the sum of its parts. Secondly it tries to fit the I.C.U. into its historical setting and to show that it was neither rootless nor, in many of its aspects, unique. Thirdly it offers an obligate of interpretation and comment that seeks to be neither importunate nor partisan.